Successive Ionic Layer Adsorption and Reaction‐Deposited Transparent Cu–Zn–S Nanocomposites as Hole Transport Materials in CdTe Photovoltaics. Issue 10 (7th September 2020) - Bastola, Ebin; Subedi, Kamala Khanal; Alfadhili, Fadhil K.; Phillips, Adam B.; Heben, Michael J.; Ellingson, Randy J.
Abstract : Evolving material science and device architectures continue to drive improvements in photovoltaic solar cell performance. Herein, the synthesis and application of p‐type transparent copper–zinc–sulfide (Cu–Zn–S) nanocomposite thin films for application as a semi‐transparent back buffer layer for cadmium telluride (CdTe) photovoltaics is reported. Earth‐abundant and low‐toxicity Cu–Zn–S films are prepared at room temperature using successive ionic layer adsorption and reaction (SILAR). Transparency in the range of 500–800 nm, low resistivity, and composition‐controlled bandgap energy offer a compelling material system for high performance as an electron reflector enabling bifacial cell design. Implementing the Cu–Zn–S hole transport material (HTM) at the CdTe back contact, without intentional introduction of Cu doping, converts simulated AM1.5 sunlight to electricity at an efficiency up to 13.2%, with an average device performance of 13.0%. Intentional Cu doping yields a best efficiency of 14.3% with open‐circuit voltage ( V OC ) of 848 mV and fill factor (FF) of 77.3% (average 14.1%). Our study shows the clear promise of this material for highly efficient and semi‐transparent back contact to CdTe solar cells. Abstract : Evolving material science and device architectures continue to drive improvements in photovoltaic solar cell performance. Cu–Zn–S (CZS) nanocomposites are optically semi‐transparent conducting materials, and their properties such as resistivity and doping level are controlled by varying material compositions. Herein, SILAR‐deposited CZS thin films are demonstrated that they can be applied as effective hole transport materials to CdTe photovoltaics.